The 2.2 Å Resolution Structure of RpiB/AlsB from Escherichia coli Illustrates a New Approach to the Ribose-5-phosphate Isomerase Reaction - Zhang, Rong-Guang (2003)
Ribose-5-phosphate isomerases (EC 5.3.1.6) interconvert ribose 5-phosphate and ribulose 5-phosphate. This reaction permits the synthesis of ribose from other sugars, as well as the recycling of sugars from nucleotide breakdown. Two unrelated types of enzyme can catalyze the reaction. The most common, RpiA, is present in almost all organisms (including Escherichia coli), and is highly conserved. The second type, RpiB, is present in some bacterial and eukaryotic species and is well conserved. In E. coli, RpiB is sometimes referred to as AlsB, because it can take part in the metabolism of the rare sugar, allose, as well as the much more common ribose sugars. We report here the structure of RpiB/AlsB from E. coli, solved by multi-wavelength anomalous diffraction (MAD) phasing, and refined to 2.2 Å resolution. RpiB is the first structure to be solved from pfam02502 (the RpiB/LacAB family). It exhibits a Rossmann-type αβα-sandwich fold that is common to many nucleotide-binding proteins, as well as other proteins with different functions. This structure is quite distinct from that of the previously solved RpiA; although both are, to some extent, based on the Rossmann fold, their tertiary and quaternary structures are very different. The four molecules in the RpiB asymmetric unit represent a dimer of dimers. Active-site residues were identified at the interface between the subunits, such that each active site has contributions from both subunits. Kinetic studies indicate that RpiB is nearly as efficient as RpiA, despite its completely different catalytic machinery. The sequence and structural results further suggest that the two homologous components of LacAB (galactose-6-phosphate isomerase) will compose a bi-functional enzyme; the second activity is unknown.